The Philosophical Foundation of the Coherence of Regulations Concerning Apartment in Indonesia - Salma Suroyya Yuniyanti (Faculty of Law, Universitas Sebelas Maret, 2020)
A state holds constitutional responsibility of embodying physical, psychological welfare, and social justice for all of its citizens. Developing apartments is one of the Indonesian government's policy to ensure the embodiment of these responsibilities. Regulation on apartment that adheres to horizontal separation principle (Horizontale scheiding beginnsel) still often leads to a range of legal issues. Accordingly, it is necessary to find out and comprehend the philosophical foundation of the coherence of regulations concerning apartment. The present study applied normative legal method with statutory and conceptual approaches. In practice, horizontal separation principle is not well-implemented and is not in line with the Basic Agrarian Law (BAL). Right of Ownership of an apartment unit (HMSRS) is a personal right and is separated from common right upon shared objects, parts, and land. This phenomenon can lead to legal issues, particularly when the secondary rights (i.e., right to use building or right to use upon the state land and right to use building or right to use upon the right to manage) are no longer extended. The implementation of horizontal separation has not provided a legal certainty for the community regarding apartment unit ownership. Accordingly, in order to provide legal certainties, the government should enact Government Regulation as further stipulation of Law no. 20 of 2011.